Kompetensi Guru IPA yang Diperlukan untuk Membelajarkan Sains di Indonesia - Yusran Khery; Muhammad Sarjan; Baiq Asma Nufida; Sukainil Ahzan (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2022)
Teacher competencies consist of pedagogical, personality, social, and professional competencies. Science educators must be able to encourage students to become lifelong students who are competent, have character, and behave in accordance with the values of Pancasila, have the competence to become democratic citizens and become superior and productive human beings, and be able to participate in sustainable and resilient global development in facing various challenges. So that to be able to integrate these values into science learning, the conception of these four competencies for science educators must be reformulated by considering the competencies needed for Education for Sustainable Development (ESD), Science Literacy, and strengthening the pupil profile of Pancasila. The results of this study show that pedagogical, personality, social, and professional competencies can be reformulated so that they are relevant to Education for Sustainable Development (ESD), Science Literacy, and strengthening the pupil profile of Pancasila learning. With the presence of this competency, the science teachers will have the ability to facilitate learning for Education for Sustainable Development (ESD), Scientific Literacy, and strengthening the profile of Pancasila learning. simultaneously through the science learning process.